Personality and Public Administration: Policymaker Tolerance of Administrative Burdens in Welfare Services. (31st May 2021) - Aarøe, Lene; Baekgaard, Martin; Christensen, Julian; Moynihan, Donald P.
Abstract: While related fields have turned to personality to understand human behavior, we know relatively little about its role and impact in public administration. We review how personality has been studied in public administration and offer an empirical test of how it relates to policymaker attitudes about administrative arrangements. Using the "Big Five" framework and a sample of elected politicians, we conduct two studies showing how personality is associated with policymaker tolerance of the administrative burdens that social welfare recipients experience. Politicians with high conscientiousness are more tolerant of burdens, suggesting that they expect similar attention to detail from others. Conversely, politicians who score higher on the trait of openness to experience are less tolerant of burdens, implying that greater empathy toward the experience of others reduces burden tolerance. These relationships hold even after controlling for political ideology, the standard explanation for burden tolerance in welfare programs .